2022
DOI: 10.1007/jhep02(2022)158
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic-invariant formulation of the NREFT three-particle quantization condition

Abstract: A three-particle quantization condition on the lattice is written down in a manifestly relativistic-invariant form by using a generalization of the non-relativistic effective field theory (NREFT) approach. Inclusion of the higher partial waves is explicitly addressed. A partial diagonalization of the quantization condition into the various irreducible representations of the (little groups of the) octahedral group has been carried out both in the center-of-mass frame and in moving frames. Furthermore, producing… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 86 publications
0
7
0
Order By: Relevance
“…It might be thought problematic that a lower cutoff is required for the nondegenerate theory-it certainly conflicts with the usual notion of a UV cutoff that one can send arbitrarily large, a point stressed recently in Ref. [25]. This is why we have also called H (i) a "transition function," because, in all derivations in the RFT approach, it has the effect of transitioning the two-particle amplitude that appears in the expressions between the two-particle K matrix K 2 at threshold (where H (i) = 1) and the two-particle amplitude M 2 far below threshold (where H (i) = 0).…”
Section: Cutoff Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…It might be thought problematic that a lower cutoff is required for the nondegenerate theory-it certainly conflicts with the usual notion of a UV cutoff that one can send arbitrarily large, a point stressed recently in Ref. [25]. This is why we have also called H (i) a "transition function," because, in all derivations in the RFT approach, it has the effect of transitioning the two-particle amplitude that appears in the expressions between the two-particle K matrix K 2 at threshold (where H (i) = 1) and the two-particle amplitude M 2 far below threshold (where H (i) = 0).…”
Section: Cutoff Functionmentioning
confidence: 99%
“…[13]). We also note that a Lorentz-invariant extension of the NREFT formalism has recently been obtained [25]. In this work we follow the RFT approach.…”
Section: Introductionmentioning
confidence: 99%
“…Simulating quantum systems in finite volume (FV), such as a cubic box with periodic boundary conditions, is a well established theoretical approach to extract information about them, going back to the early work of Lüscher [1,2,3] who showed that the real-world (i.e., infinite-volume) properties of a the system are encoded in how its (discrete) energy levels change as the size of the volume is varied. The method has become a standard approach for example in Lattice Quantum Chromodynamics (LQCD) to extract scattering information for hadronic systems, and extending it in different directions, in particular to three-body systems, is an area of active research [4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20]. Moreover, few-body approaches formulated in FV can be used to match and extrapolate LQCD results to an effective field theory (EFT) description [21,22,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, three conceptually equivalent formulations of the three-body quantization condition (an equation that connects the finite-volume energy spectrum with the infinite-volume observables in the three-particle system) have been proposed -the socalled RFT [9,11], NREFT [19,20] and FVU [21,58] approaches. A Lorentz-invariant formulation of the NREFT approach was suggested recently [46], and a three-body analog of the Lellouch-Lüscher formula, which relates the three-body decay amplitudes, measured in a finite and in the infinite volume, has been derived [59,60]. For a more detailed overview, we refer the reader to the two recent reviews on the subject [61,62].…”
Section: Introductionmentioning
confidence: 99%

Spurious poles in a finite volume

Pang,
Ebert,
Hammer
et al. 2022
Preprint
Self Cite